157 Multi-system investigation of covid-19 illness. (6th June 2022) - Mangion, Kenneth; Morrow, Andrew; Sykes, Robert; MacIntosh, Alasdair; Bagot, Catherine; Bayes, Hannah K; Bulluck, Heerajnarain; Carrick, David; Corcoran, David; Findlay, Iain; Hall Barrientos, Pauline; Ho, Antonia; et al.
Abstract : Introduction: The pathophysiology and trajectory of multiorgan involvement in post-COVID-19 syndrome is uncertain. We aimed to adjudicate the likelihood of myocarditis in post-COVID-19 patients. Methods: A prospective, longitudinal, cohort study involving post-COVID-19 patients enrolled in-hospital or early post-discharge (visit 1) and re-evaluated 28–60 days post-discharge (visit 2). Serial research blood tests (biomarkers), digital electrocardiography, and patient reported outcome measures were obtained at both visits. Chest computed tomography with pulmonary and coronary angiography, cardiovascular and renal magnetic resonance imaging, were acquired at visit 2. Results: 159 patients (mean age 55 years, 43% female) and 27 controls with similar age, sex, ethnicity, and vascular risk factors were enrolled from 22 May 2020 to 2 July 2021 and had a primary outcome evaluation. Adjudicated likelihood of myocarditis was not (n=17; 11%), unlikely (n=56; 35%), probably (n=65; 41%) or very likely (n=21; 13%). Healthcare worker status (odds ratio, 95% confidence interval: 2.99 (1.01, 8.89); p=0.048), acute kidney injury (3.26 (1.00, 10.64); p=0.050) and HbA1c(0.64 (0.42, 0.99); p=0.044) were multivariable associates of adjudicated myocarditis. During convalescence, COVID-19 was associated with worse health-related quality of life (EQ5D-5L) (p<0.001), illness perception (p<0.001), anxiety and depression (p<0.001), physical activity (p<0.001) and predicted maximal oxygen utilization (ml/kg/min) (p<0.001). These measures were associated with adjudicated myocarditis. Conclusion: The illness trajectory of COVID-19 includes persisting cardio-renal inflammation, lung damage and hemostasis activation. Adjudicated myocarditis occurred in one in eight hospitalized patients and was associated with impairments in health status, physical and psychological wellbeing during community convalescence. Conflict of Interest: Nil